2010
DOI: 10.1007/s11884-010-0065-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Treatment of Urethral Stricture Disease

Abstract: Any process causing trauma to the urethral tissue or underlying corpus spongiosum can lead to urethral stricture disease. The traditional treatment algorithm for urethral strictures, also known as the reconstructive ladder, begins with minimally invasive interventions, including urethral dilation and endoscopic urethrotomy. Inevitably, endoscopic incision and dilation fails, resulting in stricture recurrence. After the expenditure of valuable time and resources, physician and patient frustration finally leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
(72 reference statements)
0
4
0
1
Order By: Relevance
“…Open surgical repair of urethral strictures is considered to be more cost effective than repeated urethrotomy [55]. Following advances in urethral surgery and the excellent success rates of urethroplasty, reconstructive specialists now favour open surgical treatment over endoscopic treatment of most strictures [51,52,[56][57][58].…”
Section: Treatment Of Aur In Male Patientsmentioning
confidence: 99%
“…Open surgical repair of urethral strictures is considered to be more cost effective than repeated urethrotomy [55]. Following advances in urethral surgery and the excellent success rates of urethroplasty, reconstructive specialists now favour open surgical treatment over endoscopic treatment of most strictures [51,52,[56][57][58].…”
Section: Treatment Of Aur In Male Patientsmentioning
confidence: 99%
“…[9] Penile skin, prepitium and skrotal skin can be preperad as a flap. [10] There are some important points in performing flap urethroplasty. Surgery should be performed with delicate surgical equipments using absorbable, fine suture material under magnification to avoid tissue trauma and impairment of blood supply in a well-lightened operation room.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure should be completed in one stage. [10] The advantages of penile fasciocutaneous flap urethroplasty are numerous, which include using well vascularized, hairless and flexible penile skin in repairement a long urethral segment up to 150 mm, transfering easily to all parts of the urethra, being not costly, providing satisfactory results cosmetically, not destroying sexual functions, providing single stage repairement, and being suitable in some of previously circumcised men. [11][12][13] While preparing penile fasciocutaneous flap, Buck fascia is usually kept to protect neurovascular structures under the Buck fascia.…”
Section: Discussionmentioning
confidence: 99%
“…As no single technique is ideal for all types of stricture, controversy among urologist continues and currently reconstructive urologists advocating "open surgical treatment options" and not the "endoscopic management" for the majority of urethral strictures. 9,10 In United States during last decade; it is estimated that 5,000 males' patients' needs hospitalization annually. 11 A study from Pakistan 12 conducted at Sindh Institute of Urology and Transplantation (SIUT), showed that urethral stricture disease represents 3-4% of all urology diseases and 5760 patients visit annually for the dilatation, alternative treatment options and for the uroflowmetry.…”
Section: Introductionmentioning
confidence: 99%